BO`LAJAK MAKTABGACHA TA`LIM MUTAXASSISLARINI INNOVATSION KASBIY FAOLIYATGA TAYYORLASHNING PEDAGOGIK-PSIXOLOGIK XUSUSIYATLARI - AHEMEDOVA GOZZAL AHEMEDOVNA; AXMEDOVA MUXABBAT AXMEDOVNA (FAN, TA’LIM VA AMALIYOT INTEGRATSIYASI, 2021)
This article discusses the pedagogical, psychological features of the preparation of future preschool education specialists for innovative professional activities. It also sets out the issues of pedagogical practice, advanced experiences, cooperation with parents in the preparation of future preschool education specialists for innovative professional activities.